Infrared Spectroscopic Characterization of CIT-6 and a Family of *BEA Zeolites. (24th October 2013) - Tomlinson, Sean R.; McGown, Tyler; Schlup, John R.; Anthony, Jennifer L.
Abstract : Infrared spectroscopy is known to be a useful tool for identifying local structure changes in zeolites. Infrared spectroscopy is often employed to complement X-ray diffraction data. Local structure changes in zeolite CIT-6 and its zeolite beta (*BEA) analogs caused by calcination, altering framework composition, and ion exchange have been identified with mid- and far-infrared spectroscopy. Differences in the local structures of the samples were observed in mid- and far-infrared spectra, including changes in the intratetrahedral asymmetric stretch, the double-ring mode, and the intratetrahedral bending mode regions. The infrared spectra indicate that calcination or acetic acid extraction changed the structure of CIT-6 to that of zeolite beta (*BEA). Zinc ion exchange or the substitution of aluminum into the framework structure of acetic acid extracted samples retained the CIT-6 structure.